2021
DOI: 10.1136/jitc-2020-001406
|View full text |Cite
|
Sign up to set email alerts
|

Use of plasma ctDNA as a potential biomarker for longitudinal monitoring of a patient with metastatic high-risk upper tract urothelial carcinoma receiving pembrolizumab and personalized neoepitope-derived multipeptide vaccinations: a case report

Abstract: Upper tract urothelial carcinoma (UTUC) is often diagnosed late and exhibits poor prognosis. Only limited data are available concerning therapeutic regimes and potential biomarkers for disease monitoring. Standard therapies often provide only insufficient treatment options. Hence, immunotherapies and complementary approaches, such as personalized neoepitope-derived multipeptide vaccine (PNMV), come into focus. In this context, genetic analysis of tumor tissue by whole exome sequencing represents an essential d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Therefore, neoantigen‐based combination therapy may be a promising approach for UC patients with HRR alterations. A previous study reported a personalized neoepitope‐derived multipeptide vaccine complementary with immunotherapy (pembrolizumab), which induced very strong CD4+ as well as CD8+ T cell responses in patients with metastatic UC 53 . A phase Ib trial in patients with high TMB metastatic tumors demonstrated that personalized neoantigen vaccine plus anti‐PD‐1 induced neoantigen‐specific CD4+ and CD8+ T cell responses, with antitumor capability 54 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, neoantigen‐based combination therapy may be a promising approach for UC patients with HRR alterations. A previous study reported a personalized neoepitope‐derived multipeptide vaccine complementary with immunotherapy (pembrolizumab), which induced very strong CD4+ as well as CD8+ T cell responses in patients with metastatic UC 53 . A phase Ib trial in patients with high TMB metastatic tumors demonstrated that personalized neoantigen vaccine plus anti‐PD‐1 induced neoantigen‐specific CD4+ and CD8+ T cell responses, with antitumor capability 54 …”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the gene mutational profile of tumour tissue and liquid biopsies is a growing field, and much work have been done on both UCB and UTUC. Genetic markers have been identified and analyzed in different sample types (RNU specimens, URS biopsies, liquid biopsies) [ 25 , 26 , 29 , 31 , 37 ] and have been studied both in a pre-treatment diagnostic/prognostic setting and a monitoring setting [ 27 , 38 , 39 ]. For UTUC no single genetic marker has yet been identified, but studying patterns of gene mutations or gene expression seems to be the way forward.…”
Section: Discussionmentioning
confidence: 99%
“…cfDNA in urine can be used for the diagnosis of UTUC [ 37 ]. ctDNA in plasma was used for disease monitoring in a case report by Blumendeller et al [ 38 ]. A recent study on UTUC by Nakano et al [ 39 ] showed that a high fraction of preoperative ctDNA and sustained ctDNA postoperatively were associated with a worse prognosis.…”
Section: Possible Upcoming Diagnostic and Prognostic Methods ...mentioning
confidence: 99%
“…The increased concentration of ctDNA could identify patients with cancer from healthy cohorts and stratify patients in the early and advanced stages ( 16 ). Besides, the changes in ctDNA levels before and after drug treatment are related to the therapeutic effect for patients ( 17 ). Furthermore, for tumor-free patients after treatment, the concentration level of ctDNA indicates the risk of cancer recurrence ( 18 ).…”
Section: Data Features Utilized By Current Ctdna Detection Strategiesmentioning
confidence: 99%